Uji Ketahanan Api Kayu Sengon (Paraserianthes falcataria (L.) Nielsen) yang Diawetkan dengan Bahan Pengawet Natrium Silikat (Na2SiO3) - Zainul Arifin; Irvin Dayadi; Cristianus Renaldy (Fakultas Kehutanan Universitas Mulawarman, 2020)
The results of this study indicate that the average value of air dry moisture content of sengon wood is 14.081%, the air dry density is 0.326 g/m3 and oven dry density is 0.295 g/m3. The highest average retention value was at 3 days immersion with a concentration of 7% i.e. 16.161 kg/m3 and the lowest was at 1 day immersion with a concentration of 3% i.e. 5.161 kg/m3. The highest value of burn intensity at 2 days immersion with a 3% concentration i.e. 16.249% and the lowest at 1 day immersion with a concentration of 7% i.e. 6.025%. Preservation of sengon wood using natrium silicate at a concentration of 3%, 5% and 7% and immersion for 1 day, 2 days and 3 days is less effective in holding the fire rate, because the value is still below the ASTM E69 standard (2002) i.e. 7.5. The effective test of preservative (W) obtained the highest value of burn intensity at 1 day immersion with a concentration of 7% i.e. 7,490 and the lowest value at 2 days of immersion with a concentration of 3%, i.e. 3,231. The maximum temperature ranges from 206.0-291.2°C and the cooking time ranges from 206.1-607.8 seconds.